Research progress of functional microorganisms and efficient biodegradable agents in straw composting - WANG Xin, PENG Shile, ZHANG Xuyi, ZHANG Hongsen, MAO Guotao, XIE Hui, SONG Andong (Zhongguo niangzao)
Composting and fermentation of straw to produce organic fertilizer is an effective way to utilize straw resources efficiently. Adding efficient microbial degradation agents in composting can accelerate the process of straw decomposition, and can degrade complex organic compounds into simple compounds that can be utilized by plants in a short time. There are many researches on lignocellulosic degrading enzyme-producing microorganisms at home and abroad, but few researches on the application of straw degrading microorganisms. In this paper, functional microorganisms, efficient biodegradable agents of straw degradation and their application effects were introduced in detail, and the synergistic effects of multiple functional microorganisms in biodegradable straw were expounded. The research status and existing problems of multifunctional biodegradable agents of straw were analyzed, which provided a theoretical basis for the development of efficient and effective biodegradable agents of straw degradation in the future.